2021
DOI: 10.7554/elife.67878
|View full text |Cite
|
Sign up to set email alerts
|

Ir56d-dependent fatty acid responses in Drosophila uncover taste discrimination between different classes of fatty acids

Abstract: Chemosensory systems are critical for evaluating the caloric value and potential toxicity of food. While animals can discriminate between thousands of odors, much less is known about the discriminative capabilities of taste systems. Fats and sugars represent calorically potent and attractive food sources that contribute to hedonic feeding. Despite the differences in nutritional value between fats and sugars, the ability of the taste system to discriminate between different rewarding tastants is thought to be l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…Although we used null mutants in these experiments, GR39a.a is the splice form of GR39a that mediates responses to various bitter compounds (Dweck and Carlson, 2020), and GR28b, GR28b.c and GR28b.d are respectively involved in saponin detection and temperature sensing (Ni et al, 2013; Sang et al, 2019). As expected, both null mutants retained the aversion to fatty acids, as their detection may involve divergent IRs (Ahn et al, 2017; Brown et al, 2021; Masek and Keene, 2013; Sánchez-Alcañiz et al, 2018). Interestingly, the GR39a.a isoform has a large variation in copy number across various drosophilid species examined (Gardiner et al, 2008), and GR39a.a and GR28b.a are also lost in the specialist D. erecta (McBride, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although we used null mutants in these experiments, GR39a.a is the splice form of GR39a that mediates responses to various bitter compounds (Dweck and Carlson, 2020), and GR28b, GR28b.c and GR28b.d are respectively involved in saponin detection and temperature sensing (Ni et al, 2013; Sang et al, 2019). As expected, both null mutants retained the aversion to fatty acids, as their detection may involve divergent IRs (Ahn et al, 2017; Brown et al, 2021; Masek and Keene, 2013; Sánchez-Alcañiz et al, 2018). Interestingly, the GR39a.a isoform has a large variation in copy number across various drosophilid species examined (Gardiner et al, 2008), and GR39a.a and GR28b.a are also lost in the specialist D. erecta (McBride, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Matsuo et al (2007) found that losses of OBP57d and OBP57e mediate contact-mediated oviposition acceptance of fatty acids, although both olfactory and gustatory inputs are required for oviposition on Noni substrates (Álvarez-Ocaña et al, 2022). Genomic studies showed that D. sechellia lost many GR and “divergent” IR genes typically expressed in external GRNs (Crava et al, 2016; Croset et al, 2010; McBride, 2007; McBride and Arguello, 2007) which detect bitter compounds and possibly fatty acids in the generalist D. melanogaster (Ahn et al, 2017; Brown et al, 2021; Dweck and Carlson, 2019; Masek and Keene, 2013; Sánchez-Alcañiz et al, 2018; Scott, 2018). Mc Bride and Arguello (2007) suggested two explanations for the losses of chemosensory genes: 1) after specialization on M. citrifolia , D. sechellia was exposed to fewer bitter (likely harmful) compounds in their ecological niche, leading to loss of selection for chemosensory genes; 2) the loss of chemoreceptors for detection of M. citrifolia deterrents facilitated the specialization of D. sechellia on M. citrifolia .…”
Section: Introductionmentioning
confidence: 99%
“…The data suggest that gustatory and temperature-sensing neurons are required for recovery upon carbohydrate but dispensable for other nutrition such as fat or protein (see discussion). Since flies have sensory neurons that detect fatty acid (Ahn et al, 2017; Brown et al, 2021; Masek and Keene, 2013) and also amino acids-responsive neurons (Chen and Dahanukar, 2017; Croset et al, 2016; Ganguly et al, 2017; Steck et al, 2018), these neurons may control the response after fly food intake. This is likely why the sweet- or temperature-sensing-blind flies still exhibit the normal recovery after fly food intake (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila melanogaster models, gustatory receptor neurons (GRN) are housed within the gustatory sensilla, act as the primary nutrient-sensing cells, and shed light on proteins involved in rodent and human neurons ( 127 ). In the current search, five papers discussed the role of ionotropic receptor (IR) proteins, Gr64, and DmOrco in fatty acid taste in Drosophila ( 83 , 90 , 102 , 104 , 127 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tauber et al ( 127 ) reported that neurons expressing the gustatory receptor Gr64f were activated by FFA stimulation and contributed to reflexive feeding responses to fat. Additionally, Brown et al ( 90 ) found that all FA increased GR64f neural responsiveness, but the proboscis extension response to medium-chain FA is only controlled by GR64f , which suggests that short-, medium-, and long-chain FA taste discrimination occurs through different neural channels. Although only expressed in Drosophila , the involvement of these two gustatory receptors highlights the role of PLC in fat chemosensation.…”
Section: Discussionmentioning
confidence: 99%